The Effect of Firm Size, Profitability, Capital Structure and Liquidity on Stock Market Prices of Manufacturing Companies on the Indonesia Stock Exchange - Friska Darnawaty Sitorus; Medianta Nugraha Sentosa Perangin-angin; Vivian Lim (Jurnal Mantik, 2021)
Companies in Indonesia that have the most influence in the economy, one of which is a manufacturing company. The company expects the sale of a high share price to attract investors to buy it. This study aims to determine the effect of company size, structure. capital, profitability and liquidity. Regarding stock market prices in manufacturing companies on the IDX. Quantitative approach with associative form and processing statistical data through multiple linear regression. The nature of the research is a causal relationship that shows the relationship between dependent and independent variables. The population of this study was 177 companies from 2014–2019 while the research sample was 378 companies. The results of the study show that the size of the company has a significant influence on the stock market price of the IDX manufacturing company. Capital structure in manufacturing companies listed in. The IDX does not affect the stock market price. The profitability of the manufacturing company at . BEI significantly affects the stock market price. The liquidity of manufacturing companies on the IDX has no significant effect on the stock market price. Company size, capital structure, profitability and liquidity affect the stock market price of manufacturing companies on the IDX simultaneously.